Recent trends of smart agricultural systems based on Internet of Things technology: A survey. (December 2022) - Gzar, Dunia Abas; Mahmood, Ali Majeed; Al-Adilee, Maythem Kamal Abbas
Abstract: Internet of Things (IoT) technology can be used to enhance traditional approaches by combining advanced technologies with sophisticated methodologies aiming to boost agricultural production quality and quantity. The global population is rapidly growing, and the demand for food is rising accordingly. Thus, traditional agriculture will be unable to fulfill the demands of the crops. This paper aims to review the state-of-the-art contributions of smart IoT-based agriculture system design including IoT technology which presents the core framework of present and future agricultural development. Also, the basic structure of the IoT agricultural system is highlighted including the hardware and the software along with the data processing components. The potential issues systems are also investigated. The results of previous works show that the developed agricultural based-IoT systems can provide higher accuracy for making the best decision to structure a healthy farm environment. Consequently, crop production can be increased many folds. Graphical abstract: Image, graphical abstract